The Penggunaan Metode Everyone is a Teacher Here untuk Meningkatkan Kemampuan Berbicara Siswa Kelas XI SMK Negeri 1 Pasarwajo - Fadila Umally; La Mido; Sanaria Maneba (English Education Department, 2021)
Problem statement in this research was whether the use of everyone is a teacher here increase students speaking ability on eleventh grade students at SMK Negeri 1 Pasarwajo. Objective in this research was to found out the significant increasing of students speaking ability by using everyone is a teacher here compared using conventional method in class XI students.This research used quasy experimental research with quantitative approach. Population in this research were all eleventh grade students of SMK Negeri Satu Pasarwajo with total population were 64 students. This research used random sampling technique. Data collection in this research was carried out using research instrumen of test. The test was collect administering pre-test, treatment, and post-test. Pre-test and post-test was given to know the students speaking ability before get treatment and after get treatmen. The data obtained in this research were analyzed by descriptive statistic and inferential statistic. Based on the finding of the research, the research obtained the mean value of pretest in Experimental class was 46.66 and the mean value of posttest in Experimental class was 63.57, the mean value of pretest in Control class was 45.57 and the mean value of posttest in Control class was 45.85. The significant value was 0.000, t-count was greater than t-table (8.336>2.021). Based on the result, the researchers conclude that there is an improvement in students’ speaking ability using the method of of everyone is a teacher here.